Development of Student Worksheets Using Question Probing Scaffolding with Perplexity AI to Enhance Creative Thinking Skills and Mathematical Problem-Solving Abilities - Rina Aliyah; Farida Farida; Wawan Gunawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The main objective of this study is to develop teaching materials in the form of Student Worksheets using Question Probing Scaffolding with Perplexity AI to encourage creative thinking and mathematical problem-solving skills in the subject of Relations and Functions. The type of research used was Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development procedure. This research was conducted in two schools, namely SMP Muhammadiyah 3 Bandar Lampung and SMPN 1 Menggala Timur in the 2024/2025 academic year. The research instruments used were validation questionnaires, tests, and documentation. The data obtained was then analyzed using quantitative and qualitative data analysis techniques. Based on the feasibility test by the validator, the student worksheets using Question Probing Scaffolding was categorized as very feasible. Based on the student response questionnaire, the student worksheets using Question Probing Scaffolding was categorized as very interesting. The N-Gain calculation results show that the use of student worksheets based on Question Probing Scaffolding produces an increase in creative thinking and problem-solving abilities in the high category. The t-test also shows a significant difference between the pre-test and post-test scores, proving that the developed student worksheets is feasible and effective for use in Relations and Functions material. Overall, this student worksheets is considered practical, easy to implement, and able to improve the learning outcomes of junior high school students.